From Behaviorism to Connectivism of Modern E-Learning - Zbigniew Meger (Center for Open and Multimedia Eduacation of the University of Warsaw, 2012)
Wider use of e-learning methods and universality of learning platform encourage to running learning processes in different forms and to preparing new teaching materials. However, it appears that such materials are usually prepared in the simplest form of programmed learning course, where knowledge is transmitted in form of programmed instruction without or only with a weak feedback from the learner. Meanwhile, in the past four decades are developing cognitive methods, which are only slightly reflected in nowadays techniques and methods of distance learning. However, it appears in the last years, that the important role in education can play constructivism, whose ideas can be also implement in distance learning environment. All of these trends is trying to cover the theory of connectivism, and glimpse of this theory can indicate the opportunities and threats of modern e-learning.